Expression patterns of the chromosome 21 MicroRNA cluster (miR-99a, miR-125b and let-7c) in chorioamniotic membranes. (January 2017) - Modi, Bhavi P.; Washington, Sonya; Walsh, Scott W.; Jackson-Cook, Colleen; Archer, Kellie J.; Strauss, Jerome F.
Abstract: Trisomy 21 (T21) is the most common chromosome abnormality in humans and is associated with a spectrum of phenotypes, including cognitive impairment, congenital heart defects and immune system defects. In addition, T21 is also associated with abnormalities of fetal membranes including chorioamniotic separation, delayed fusion of the chorioamniotic membranes, defects in syncytiotrophoblast formation, as well as amniocyte senescence. There is evidence indicating miRNAs encoded by sequences on chromosome 21 (Chr-21) are involved in several of the cognitive and neurological phenotypes of T21, but the role of Chr-21 derived miRNAs in fetal membrane abnormalities associated with T21 has not been investigated. In the current study, we determined the expression patterns of three miRNAs derived from a cluster on Chr-21 – hsa-miR-99a, hsa-miR-125b and hsa-let-7c in chorioamniotic membranes obtained from term pregnancies with spontaneous rupture (n = 20). Tissue and location specific expression patterns within the chorioamniotic membranes were identified. The rupture zone in the choriodecidua had distinct expression patterns compared to other fetal membrane locations. Despite the increased gene dosage associated with T21, the expression of all three miRNAs was reduced in cultured T21 amniocytes as compared to cultured euploid amniocytes. In silico analysis of experimentally validated targets of the three miRNAs suggest these Chr-21 derived miRNAs play a potential role in fetal membrane rupture and the fetal membrane defects associated with T21. Highlights: Expression of Chromosome 21 miRNAs (miR-99a, miR-125b, let-7c) was investigated. Altered expression of these miRNAs in trisomy 21 amniocytes was established. Tissue/location specific expression patterns in fetal membranes were observed. Roles in fetal membrane abnormalities associated with trisomy 21 are suggested.